Dietary fiber, energy intake and nutritional status during the treatment of children with chronic constipation - Speridião,P.G.L. (2003)
The present prospective study was carried out to determine dietary fiber and energy intake and nutritional status of children during the treatment of chronic constipation. Twenty-five patients aged 2 to 12 years with chronic constipation were submitted to clinical evaluation, assessment of dietary patterns, and anthropometry before and after 45 and 90 days of treatment. The treatment of chronic constipation included rectal disimpaction, ingestion of mineral oil and diet therapy. The standardized diet prescribed consisted of regular food without a fiber supplement and met the nutrient requirements according to the recommended daily allowance. The fiber content was 9.0 to 11.9 g for patients aged less than 6 years and 12.0 to 18.0 g for patients older than 6 years. Sixteen patients completed the 90-day follow-up and all presented clinical improvement. The anthropometric variables did not change, except midarm circumference and triceps skinfold thickness which were significantly increased. Statistically significant increases were also found in percent calorie intake adequacy in terms of recommended daily allowance (55.5 to 76.5% on day 45 and to 68.5% on day 90; P = 0.047). Percent adequacy of minimum recommended daily intake of dietary fiber (age + 5 g) increased during treatment (from 46.8 to 52.8% on day 45 and to 56.3% on day 90; P = 0.009). Food and dietary fiber intake and triceps skinfold thickness increased during follow-up. We conclude that the therapeutic program provided a good clinical outcome.